KAJIAN HIDROMORFOLOGI DANAU MARTUBUNG INDAH KECAMATAN MEDAN LABUHAN SUMATERA UTARA (Hydromorphology Study of Martubung Indah Lake Distric of Medan Labuhan North Sumatera) - Dita Agnesia; Darma Bakti; Zulham Apandy Harahap (AQUACOASTMARINE, 2017)
Lake is the water mass that occupied the basin wide and surrounded by land and can be formed both natural and artificial. Martubung Indah Lake is an artificial lake in PERUMNAS Griya Martubung, North Sumatera. Morphometry data is required in determining layers lake and also determined the lake ability can be used by the public. The purpose of this research was to discover the hydromorphometry aspects Martubung Indah Lake. This research was held from May to June 2016. Collecting data in this research were depth, stream flow, lake width, water quality, and around the lake. These data were processed using ArcMap. The result of this research Martubung Indah lake has 100.532,88 m2 wide scale, maximum length of 509,44 m, maximum width 197,34 m, circumference of 1301.52 m. Maximum depth of 1.5 m, with flat basic shape of the lake. The capacity of Martubung Indah lake which can be used bythe public is 68.657,77 m3 of water volume, stream flow around 0.09 L/s - 0.13 L/s, residence time of water ± 794 - 795 days, the brightness of the water approximately 0.10 to 0.55 m, and Martubung Indah Lake is including into the oligothropic lake.Keywords: Martubung Indah Lake, lake hydromorphometry, the status of the lake.